1985
DOI: 10.1136/bmj.291.6496.619
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRw6 as a risk factor for active cytomegalovirus but not for herpes simplex virus infection after renal allograft transplantation.

Abstract: To study genetically determined susceptibility to cytomegalovirus and herpes simplex virus infections in patients given renal transplants a prospective study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
(2 reference statements)
1
7
1
Order By: Relevance
“…disease 43 + 19 REU. These differences are not statistically Like Roenhorst et al [17], we also found an increased risk of significant. In all CMV-negative recipients IgG anti-CMV was CMV infection when donor and/or patient had the HLA-DRw6 negative shortly after Tx. phenotype.…”
Section: Introductionsupporting
confidence: 37%
“…disease 43 + 19 REU. These differences are not statistically Like Roenhorst et al [17], we also found an increased risk of significant. In all CMV-negative recipients IgG anti-CMV was CMV infection when donor and/or patient had the HLA-DRw6 negative shortly after Tx. phenotype.…”
Section: Introductionsupporting
confidence: 37%
“…We and others have observed variations in the incidence, severity, and consequences of viral activity in solid organ transplantation related to HLA matching (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Several authors have observed that the incidence of CMV disease was more common when certain HLA antigens were present (3,6 -8,10 -13).…”
mentioning
confidence: 99%
“…Roenhorst et al (1985) found that cadaveric renal transplant recipients positive for HLA-DRw6, compared to those negative for this antigen, showed a significantly earlier and higher frequency of CMV infection detected serologically. No relationship to any other HLA antigens were found, including A and B antigens.…”
Section: Cytomegalovirus Lnfection Graft Rejection and Allograft Rementioning
confidence: 85%